The Effect Of Viral Marketing And Electronic Word Of Mouth On Purchase Decisions Of Tiktok Shop Application Users - Maria Sonda Baco; Mey Enggane Limbongan (Proceeding of The International Conference on Economics and Business, 2022)
The research problem is how much influence Viral marketing and electronic word of mouth have on purchasing decisions for users of the tiktok shop application. This study aims to determine the effect of viral marketing and electronic word of mouth on purchasing decisions among users of the Tiktok shop application for students of the Faculty of Economics, UKI Toraja, class of 2022. The type of data in this research is primary data obtained from a questionnaire of respondents, namely students of the UKI Faculty of Economics. Toraja class of 2022 and secondary data obtained from previous research and journals needed in this study. The method in this study is multiple linear analysis. The results of calculations with the T test obtained on the variable viral marketing t count 1.279 < t table 2.002, E-WOM t count 2.149 > t table 2.002 and from the results of the Fcount test 2.492 < 3.16 and the conclusion from the results of this study that viral marketing and electronic word of mouth does not have a significant and simultaneous influence on purchasing decisions on users of the tiktok shop application.